2011
DOI: 10.1016/j.actbio.2011.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional magnetic mesoporous bioactive glass scaffolds with a hierarchical pore structure

Abstract: Hyperthermia and local drug delivery have been proposed as potential therapeutic approaches for bone defects resulting from malignant bone tumors. The development of bioactive materials with magnetic and drug delivery properties may potentially meet this target. The aim of this study was to develop a multifunctional mesoporous bioactive glass (MBG) scaffold system for both hyperthermic and local drug delivery applications. To this end iron (Fe)-containing MBG (Fe-MBG) scaffolds with a hierarchical large pores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
118
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(130 citation statements)
references
References 38 publications
11
118
0
1
Order By: Relevance
“…The in vitro studies using B ion-doped implants showed no cytotoxic effects in bone-marrow mesenchymal stem cells, and ions were gradually released into the culture medium, resulting in enhanced cell proliferation and alkaline phosphatase (ALP) activity and mineralization 107) . Sr, Fe, Mg, Zn or Zr-doped BGNs and their nanocomposite enhanced cell proliferative activity and apatite formation ability as well as the expression of bone-related genes (osteocalcin and ALP) and dentin-related genes (DSPP and DMP) in human bone-marrow mesenchymal stem cells and pulp stem cells 108,109) . Li-doped BGNs and their nanocomposites in the use of human periodontal ligament-derived cells improved cementum formation of the cells and thereby mineralization during periodontal regeneration, which is responsible for linking the roots and surrounding alveolar bone 110) .…”
Section: Angiogenesismentioning
confidence: 99%
“…The in vitro studies using B ion-doped implants showed no cytotoxic effects in bone-marrow mesenchymal stem cells, and ions were gradually released into the culture medium, resulting in enhanced cell proliferation and alkaline phosphatase (ALP) activity and mineralization 107) . Sr, Fe, Mg, Zn or Zr-doped BGNs and their nanocomposite enhanced cell proliferative activity and apatite formation ability as well as the expression of bone-related genes (osteocalcin and ALP) and dentin-related genes (DSPP and DMP) in human bone-marrow mesenchymal stem cells and pulp stem cells 108,109) . Li-doped BGNs and their nanocomposites in the use of human periodontal ligament-derived cells improved cementum formation of the cells and thereby mineralization during periodontal regeneration, which is responsible for linking the roots and surrounding alveolar bone 110) .…”
Section: Angiogenesismentioning
confidence: 99%
“…We have developed a series of MBG scaffolds with varying compositions for drug delivery and bone tissue engineering application. [98][99][100][101] The prepared scaffolds possess large pores with the size of 300-500 µm, and well-ordered mesopores with the pore size of 5 nm (Figure 3). The advantages of the MBG scaffolds prepared by polyurethane sponge template method include their highly interconnective pore structures and controllable pore size (porosity), while the disadvantage is the low mechanical strength of the material.…”
Section: Nanotechnology In Bone Regenerationmentioning
confidence: 99%
“…In response to alternating magnetic fields, heat is generated to eliminate cancerous tissues around the bone defects [7][8][9]. Local drug delivery can also be added to prevent the transportation of cancer cells to other sites [9][10][11]. To realize the commercial potential of these multifunctional bioactive glasses, attempts have been made to determine the influence of process parameters on the distribution of pores, magnetic properties and bioactivity.…”
Section: Introductionmentioning
confidence: 99%
“…By incorporating magnetic nanoparticles, the obtained bioactive glasses can be implemented in local hyperthermia treatments. In response to alternating magnetic fields, heat is generated to eliminate cancerous tissues around the bone defects [7][8][9]. Local drug delivery can also be added to prevent the transportation of cancer cells to other sites [9][10][11].…”
Section: Introductionmentioning
confidence: 99%